2020
DOI: 10.3389/fnagi.2020.581524
|View full text |Cite
|
Sign up to set email alerts
|

Analyses Mutations in GSN, CST3, TTR, and ITM2B Genes in Chinese Patients With Alzheimer’s Disease

Abstract: Amyloid protein deposition is a common mechanism of hereditary amyloidosis (HA) and Alzheimer's disease (AD). Mutations of gelsolin (GSN), cystatin C (CST3), transthyretin (TTR), and integral membrane protein 2B (ITM2B) genes can lead to HA. But the relationship is unclear between these genes and AD. Genes targeted sequencing (GTS), including GSN, CST3, TTR, and ITM2B, was performed in a total of 636 patients with clinical AD and 365 normal controls from China. As a result, according to American College of Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“… 60 Interestingly, our previous study demonstrated that mutations in GSN may contribute to the pathogenesis of AD. 22 This present study revealed that variants in GSN were suggestively correlated not only with AAO but also with MMSE scores, further implicating the GSN gene in AD development. ITM2B gene encodes integral membrane protein 2B, which can interact with Aβ‐precursor protein and inhibit its processing.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“… 60 Interestingly, our previous study demonstrated that mutations in GSN may contribute to the pathogenesis of AD. 22 This present study revealed that variants in GSN were suggestively correlated not only with AAO but also with MMSE scores, further implicating the GSN gene in AD development. ITM2B gene encodes integral membrane protein 2B, which can interact with Aβ‐precursor protein and inhibit its processing.…”
Section: Discussionsupporting
confidence: 69%
“…Eight VaD‐associated genes, NOTCH3 , HTRA1 , TREX1 , GLA , COL4A1 , CST3 , GSN , and ITM2B , were finally seclected. 18 , 19 , 20 , 21 , 22 …”
Section: Methodsmentioning
confidence: 99%
“…Blood samples (10 mL per subject) were obtained by venipuncture from each subject and transferred to ethylenediaminetetraacetic acid (EDTA) tubes. Genomic DNA was isolated from peripheral blood leukocytes using a standard protocol [ 17 ]. All isolated DNA samples were measured for quality and quantity by a fluorometer and normalized to 50 ng/μL.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, frameshift mutations in the GSN gene in patients with AD were only observed in Han populations. Among the reported mutations in the GSN gene, there are three frameshift mutations (A34fs, K346fs and P3fs8 26), all of which were reported in Han populations, suggesting geographical heterogeneity of the GSN mutations. For missense variants, we failed to identify significant enrichment of these missense variants across the GSN gene in patients with AD compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
“…The well-known pathogenic missense mutations of the GSN gene have been reported to be associated with familial amyloidosis of the Finnish type (FAF), which mainly manifests as corneal lattice dystrophy, cranial neuropathy, peripheral neuropathy and cutis laxa 7. Recently, we reported patients with GSN frameshift mutations were characterised by the typical AD phenotype 8. Among the five patients with AD (cases 1–5) with GSN frameshift mutations, unfortunately, only the patient with the K346fs mutation (case 1) accepted Pittsburgh compound ([ 11 C]PIB)positron emission tomography (PET) examination and was confirmed to have cerebral Aβ deposition; however, no patient agreed to undergo skin biopsy, which is of great help in differentiating the diagnosis of FAF 8.…”
Section: Introductionmentioning
confidence: 99%